2001
DOI: 10.1161/01.cir.103.4.485
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Cardiac Ryanodine Receptor (RyR2) Gene in Familial Polymorphic Ventricular Tachycardia

Abstract: Background-Familial polymorphic ventricular tachycardia is an autosomal-dominant, inherited disease with a relatively early onset and a mortality rate of Ϸ30% by the age of 30 years. Phenotypically, it is characterized by salvoes of bidirectional and polymorphic ventricular tachycardias in response to vigorous exercise, with no structural evidence of myocardial disease. We previously mapped the causative gene to chromosome 1q42-q43. In the present study, we demonstrate that patients with familial polymorphic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
287
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(302 citation statements)
references
References 34 publications
4
287
0
2
Order By: Relevance
“…These findings therefore are in accord with the clinical observation that patients with mutated RyRs display a catecholaminergic polymorphic ventricular tachycardia and therefore show arrhythmias only during adrenergic stimulation. 11,12 Our results show that an acute increase of RyR opening can cause diastolic Ca 2ϩ release until SR Ca 2ϩ decreases. It is therefore possible that clinically an acute sensitization of the RyR would be arrhythmogenic.…”
Section: Implications For Arrhythmogenesismentioning
confidence: 65%
See 1 more Smart Citation
“…These findings therefore are in accord with the clinical observation that patients with mutated RyRs display a catecholaminergic polymorphic ventricular tachycardia and therefore show arrhythmias only during adrenergic stimulation. 11,12 Our results show that an acute increase of RyR opening can cause diastolic Ca 2ϩ release until SR Ca 2ϩ decreases. It is therefore possible that clinically an acute sensitization of the RyR would be arrhythmogenic.…”
Section: Implications For Arrhythmogenesismentioning
confidence: 65%
“…8 This is thought to be responsible for the arrhythmogenic diastolic Ca 2ϩ release in conditions such as digitalis intoxication 6,7,9 and reperfusion following ischemia; 10 and (2) changes in the properties of the RyR. Mutations in the human RyR [11][12][13] or accessory proteins such as calsequestrin 14 increase susceptibility to lethal arrhythmias such as catecholaminergic polymorphic ventricular tachycardia. It has also been suggested that in heart failure, the open probability (P o ) of the normal RyR may be increased by protein kinase A-dependent phosphorylation and that this may be arrhythmogenic.…”
mentioning
confidence: 99%
“…Further, alterations in calcium signaling through ryanodine receptor mutations have been shown to cause sudden cardiac death and catecholaminergic polymorphic ventricular tachycardia. Therefore, calcium signaling irregularities might be a component of the frequent sudden cardiac death seen in HCM [2,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Shou et al, (1998) are consistent with the finding that paediatric organ transplant patients given high doses of FK506 developed hypertrophic cardiomyopathy associated with clinically severe heart failure (Atkinson, 1995). Further, genetically transmitted mutations in the hRyR2 gene causes stress-induced bidirectional ventricular tachycardia (Laitinen et al, 2001;Priori et al, 2001), leading to cardiac arrest and sudden death. It has been suggested that these mutations disrupt the FKBP12.6 association, leaving RyR2 in an open state (Marks, 2002).…”
mentioning
confidence: 99%